2014
DOI: 10.1007/s11998-014-9628-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ink transfer on print mottle in shrink films

Abstract: The gravure printing process is considered a pioneer in long run package printing jobs, offering exceptional print quality teamed with high quantities. Shrink films, primarily polyvinyl chloride (PVC) and polyethylene terephthalate-glycol modified (PET-G) are extensively printed using the rotogravure printing process. The intricacies of the printing process and the complex nature of the interactions between the substrate, ink, and printing press, if not studied and controlled, can contribute to unnecessary var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Since all wetting coefficients in the TLC/UVF systems (except TLC-UVF on CB substrate with high wetting coefficient of 12.73 mJ/m 2 ) presented negative values, it can be concluded that the wetting between the layers was generally not complete. This occurrence is generally not favourable, but a negative wetting coefficient in the printing process can decrease the unevenness of the print called mottling, resulting with the improved print quality [43].…”
Section: Surface Free Energy and Adhesion Parametersmentioning
confidence: 99%
“…Since all wetting coefficients in the TLC/UVF systems (except TLC-UVF on CB substrate with high wetting coefficient of 12.73 mJ/m 2 ) presented negative values, it can be concluded that the wetting between the layers was generally not complete. This occurrence is generally not favourable, but a negative wetting coefficient in the printing process can decrease the unevenness of the print called mottling, resulting with the improved print quality [43].…”
Section: Surface Free Energy and Adhesion Parametersmentioning
confidence: 99%
“…Nevertheless, these cerium conversion coatings have some disadvantages such as the crack of the film and the loose structure, [9] which make the coating providing limited protection to the substrates. In recent years, an intense research is ongoing to develop environmentally and friendly conversion treatment processes to improve the corrosion resistance in corrosive media, including the cerium conversion coatings with alkaline cleaning and activation, [10] phosphate post-treatment, [9,11] water solution gelatin addictive [12,13] and so on. Despite so many researches devoted to the optimization of the cerium conversion coating preparation technology, the problem of the poor adhesion ability has not been resolved yet.…”
Section: Introductionmentioning
confidence: 99%